Faktor Sokongan Individu Terhadap Kecemerlangan Wanita Bekerjaya dan Berumah Tangga - Hamzah, Naemah; Mustari, Mohd Ismail; Basiron, Bushrah (Sains Humanika, 2013)
The world today witnesses a significant increase in the needs of women engagement in the workforce, particularly in successful economic transformation of the country. Women today are not only seen as a support group, but also as decision makers; in line with the government’s aspiration. Thus, women today need the right inspiration based on Sharia in achieving success in their careers and households. Data were collected through qualitative design using in-depth interviews of women working JUSA (VK7) in the public sector and document analysis involves fiqh books, journals, papers and documents of the study participants as data support. Interview support data also includes the interviews of husbands, children, employers and colleagues to create a triangulation of data. The findings were analysed using Nvivo 7.0. This research has produced models of supporting factors in the success of career women and homemakers that involves skills that is essential and individual supporting factors.